2020
DOI: 10.21873/anticanres.14251
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Quantitative Interferon-gamma Levels in Non-small-cell Lung Cancer Patients' Response to Immune Checkpoint Inhibitors

Abstract: Background/Aim: We aimed to study the association between the quantitative interferon-gamma (IFNγ) levels and clinical outcomes in non-small-cell lung cancer (NSCLC) patients receiving immune checkpoint inhibitors (ICIs). Patients and Methods: Sample collection for IFN-γ release assay (IGRA) was performed within 14 days before treatment (T1), on day 22±7 (T3), and on day 43±7 (T4). The stored specimens over 10 IU/ml in IGRA were re-examined using the dilution method (with saline as the dilution medium). The pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 10 publications
2
13
0
Order By: Relevance
“…Huang et al (6) has previously reported that a higher pretreatment PHA-stimulated IFN-γ response (high-PHA) was associated with better survival among advanced NSCLC patients treated with chemotherapy. These findings are similar to those of our previous study (5), in which we suggested that Eruption 10 1 1 2 1 0 8 0 1 Thyroid dysfunction 7 0 0 3 0 0 4 0 0 Interstitial Pneumonitis 1 2 3 1 0 0 0 2 3 Colitis 1 3 1 0 0 1 1 3 0 Myositis 1 high-PHA, which may reflect a better immunological status, is associated with improved progression-free survival. Previous studies have identified several inflammation/ nutrition biomarkers as prognostic factors for cancer.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Huang et al (6) has previously reported that a higher pretreatment PHA-stimulated IFN-γ response (high-PHA) was associated with better survival among advanced NSCLC patients treated with chemotherapy. These findings are similar to those of our previous study (5), in which we suggested that Eruption 10 1 1 2 1 0 8 0 1 Thyroid dysfunction 7 0 0 3 0 0 4 0 0 Interstitial Pneumonitis 1 2 3 1 0 0 0 2 3 Colitis 1 3 1 0 0 1 1 3 0 Myositis 1 high-PHA, which may reflect a better immunological status, is associated with improved progression-free survival. Previous studies have identified several inflammation/ nutrition biomarkers as prognostic factors for cancer.…”
Section: Discussionsupporting
confidence: 91%
“…Firstly, IGR level directly examines the activity of viable T cells; therefore, it is an index of immune function. Secondly, IGR levels change dynamically during ICI-tx, depending on the immune status of the patients as shown in our previous studies (4,5). Thus, while other markers for ICI-tx efficacy are static biomarkers, IGR levels are dynamic, and more accurate.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…9 Interferon-γ (IFN-γ) is released from T cells as part of their normal activation, and IFN-γ concentrations are reportedly related to ICI treatment response. 10 Furthermore, disruption of the IFN-γ receptor signaling pathway can lead to resistance to anti-PD-L1 therapy. 11 An IFN-γ releasing assay (IGRA) can be used to identify Mycobacterium tuberculosis based on T-cell production of IFN-γ in response to stimulation with tuberculosis-specific antigens (TBAgs).…”
Section: Introductionmentioning
confidence: 99%